PENGARUH CINTRA MEREK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PT. PEGADAIAN (PERSERO) UPC MANCASAN YOGYAKARTA - Setiawan, Edi; Dahlan, Septiani MS; Jaya, I Made Laut Mertha (PRIMA EKONOMIKA, 2022)
The purpose of this study was to determine the effect of partially or simultaneously brand image and service quality on customer satisfaction of PT. Pawnshop (Persero) UPC Mancasan Yogyakarta. The type of research used in this study is a type of quantitative research that aims to confirm the data obtained. The sampling technique used is purposive sampling with the number of respondents as many as 100 customers. This research was conducted at PT. Pawnshop (Persero) UPC Mancasan Yogyakarta. The technique of collecting data is using a questionnaire technique. The data obtained were then processed using SPSS version 23. This analysis includes instrument testing, classical assumption test, multiple linear regression, hypothesis testing and F test, and coefficient of determination test (R Square). Based on the t-test data analysis conducted in this study, it can be seen that the brand image variable has no partial significant effect on customer satisfaction with a significance value of 0.170 > 0.05, and the service quality variable has a partially significant effect on customer satisfaction with a significance value of 0.001 < 0.05. While the results of the F test can be seen that the variable brand image and service quality simultaneously have a significant effect on customer satisfaction with a significance value of 0.002 <0.05. While the effect of the two variables on customer satisfaction if presented is 62.4% and the remaining 37.6% is explained by other variables that are not included in the statement in this study. Keywords: Customer Satisfaction, Brand Image, Service Quality.